Small scale agriculture continues to drive deforestation and degradation in fragmented forests in the Congo Basin (2015-2020) - Shapiro, A.; d’Annunzio, R.; Desclée, B.; Jungers, Q.; Kondjo, H.K.; Iyanga, J.M.; Gangyo, F.I.; Nana, T.; Obame, C.V.; Milandou, C.; Rambaud, P.; Sonwa, D.J.; et al. (Elsevier, 2023)
The Central African region hosts the largest continuous tract of forest in Africa, regulating global climate while providing essential resources and livelihoods for millions of people and harbouring extensive biodiversity. Extractive industries, infrastructure development and industrial agriculture have often been cited as major threats to these forests and are expected to increase. A regional collaborative effort has produced the first systematically validated remote sensing assessment of deforestation and degradation drivers in six central African countries for the 2015–2020 time period. Multiple, overlapping drivers are assessed through visual interpretation and show that the rural complex, a combination of small-scale agriculture, villages, and roads contributes to the majority of observed deforestation and degradation. Industrial drivers such as mining and forestry are less common, although their impacts on carbon and biodiversity could be more permanent and significant than informal activities. Artisanal forestry is the only driver that is observed to be consistently increasing over the study period. Our assessment produces information relevant for climate change mitigation and land use planning which requires detailed information on multiple direct drivers to target specific activities and investments.